Constrained saccharides: a review of structure, biology, and synthesis. Issue 3 (7th March 2018) - Rodriguez, Jacob; O'Neill, Sloane; Walczak, Maciej A.
Abstract : Conformationally restricted natural products containing hydrocarbon tethers attached to an oligosaccharide chain display intriguing structural and biological properties. Abstract : Review primarily covers from 1995–2018 Carbohydrate function, recognized in a multitude of biological processes, provides a precedent for developing carbohydrate surrogates that mimic the structure and function of bioactive compounds. In order to constrain highly flexible oligosaccharides, synthetic tethering techniques like those exemplified by stapled peptides are utilized to varying degrees of success. Naturally occurring constrained carbohydrates, however, exist with noteworthy cytotoxic and chemosensitizing properties. This review highlights the structure, biology, and synthesis of this intriguing class of molecules.